Developments in synthesis, characterization, and self‐assembly of polycarbodiimide systems. Issue 18 (27th March 2017) - Mammoottil, Nimmy R.; Reuther, James F.; Siriwardane, Dumindika A.; Kulikov, Oleg V.; Novak, Bruce M.
ABSTRACT: Described herein is a comprehensive survey on the most recent advancements in polycarbodiimide synthetic methodologies, structure determination, property design, and self‐assembly. In particular, the 15 N‐isotopic enrichment of polycarbodiimides is detailed along with the use of 15 N NMR to identify the regioregularity and mechanism of chiroptical switching in polycarbodiimides. Furthermore, the new Ni(II) mediated "living" polymerization is explained along with its utilization in the incorporation of polycarbodiimides into block copolymers, graft copolymers, and star polymers. Finally, we review the recent discoveries focusing on the highly tunable self‐assembly behaviors of polycarbodiimide homopolymers and copolymers. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2915–2934 Abstract : This highlight focuses on the most recent advancements in polycarbodiimide chemistry. Most notably, it describes the newest developments in microstructure determination, property design, synthetic methodology, and self‐assembly of polycarbodiimides.